Complications of cerebral angiography in patients with symptomatic carotid territory ischaemia screened by carotid ultrasound. - Davies, K N (1993)
After nearly 40 years, carotid endarterectomy has been shown to be of benefit to patients with symptomatic carotid territory ischaemia and greater than 70% stenosis of the relevant internal carotid artery. Cerebral angiography is performed before surgery and is not without risk. These risks must be added to those of surgery before recommending the procedure to patients. The study evaluated the local, systemic and neurological complications following digital subtraction angiography with selective catheterisation of the carotid arteries in 200 patients presenting to a cerebrovascular clinic for assessment of cerebral ischaemia. All patients had carotid ultrasound screening before angiography to screen out those with normal arteries or mild disease (less than 30% stenosis of symptomatic internal carotid artery). Complications occurred in 28 patients. There were six (3%) local, two (1%) systemic and 20 (10%) neurological complications. Seventeen neurological complications occurred within 24 hours and there were three late complications (24-72 hours). Neurological complications occurred more frequently when angiography was performed by a trainee rather than a consultant neuroradiologist (p < 0.01). The neurological complications were transient (resolved within 24 hours) in 10/200 (5%), reversible (resolved within seven days) in two (1%) and permanent in 8/200 (4%). Two patients died after a stroke and two other patients suffered a disabling stroke. At 24 hours post angiography the permanent (persisting beyond seven days) neurological complication rate was 2.5%. The incidence of total neurological complications and post angiographic strokes was higher in patients with greater than 90% stenosis of the symptomatic internal carotid artery (p < 0.001). The increased use of non-invasive Doppler duplex screening will reduced the absolute number of patients put at risk of angiography, yet the rate of post angiographic complications is likely to increase as patients with severe stenosis of the symptomatic internal carotid artery are probably most at risk of complications and have most to gain from carotid endarterectomy.